Dongeng/Cerita Dalam Perspektif Pendidikan - Muhammad Hanif (Jurnal Pendidikan, 2010)
Folktales which had become favourable choice for children to enjoy mainly before sleep are now undergoing degradation, even they become strange things and of ignorance for them. They do not need them anymore in the replacement of play stations, VCD players, and the likes. Inspite of children’s ignorance against folktales, they fully contain moral values which are needed for our next generation to manage themselves better in leading the world. For this reason, folktales educationally need to be transformed and nurtured to children. In line with the progress of information technology, folktales can be packed in such a way to attract youngsters still in regard to the essence of their moral contents. The package of folktales can be in the forms of novels, comic-strips, film-strips, pictures, or electronic cinema which in turn can be served for children through educational centres, suveniers, students’ stationaries. The role of the government is not to mention important in support of the implementation of them to children through its budget or legal hands to in-built curriculum.